Membrane-Assisted Dark Fermentation for Integrated Biohydrogen Production and Purification: A Comprehensive Review - Octavio García-Depraect; Laura Vargas-Estrada; Raúl Muñoz; Roberto Castro-Muñoz (Fermentation)
The aim of this review is to provide a comprehensive analysis of the membrane-assisted dark fermentation process for bioH2 production and purification. This review initially analyses the need for and the current state of the art in H2 production through dark fermentation, evaluating the research landscape and the maturity level of the technology. Key factors influencing the dark fermentation process are then examined, along with emerging research trends in membrane-assisted fermentative H2 production systems. This review subsequently addresses the challenges inherent to dark fermentation and explores potential opportunities to enhance H2 production efficiency. Special attention is given to membrane technology as a promising strategy for process intensification in bioH2 production and recovery. Finally, this review provides an in-depth discussion of inorganic membranes, mixed matrix membranes (MMMs), and thin and ultrathin membranes, evaluating each membrane type in terms of its advantages, limitations, and purification performance. This review offers valuable insights into intensifying the dark fermentation process by leveraging membrane technology to enhance bioH2 production and purification efficiency.